A study to correlate trends in perfusion index and bispectral index for assessment of depth of anesthesia: A cross-sectional study - Karthik Raj M; Shalini Jain; Manish Banjare; Nidhi Sharma (Asian Journal of Medical Sciences)
Background: Accurate anesthesia depth monitoring is crucial for patient safety. Bispectral index (BIS) measures brain activity, whereas perfusion index (PI) reflects peripheral blood flow and sympathetic tone. BIS is a gold standard but is limited by cost and interference, whereas PI is a simpler, more accessible alternative.